Assessing rural populations’ barriers to mental healthcare and perceptions towards prescription digital therapeutics: a cross-sectional survey - Danon, Grace; Dunn, Cody E.; Robins, Michael; Nagendra, Arundati; Strand, Chuck; Palko, Lisa; Colborn, Adam; Menjivar, Jackie; Saber, Junko (Frontiers in Digital Health, 2025)
IntroductionPrescription Digital Therapeutics (PDTs) hold unique potential to improve mental health in underserved rural areas. However, potential users' perceptions towards PDTs and community-specific differences in barriers to care are not well-understood.MethodsWe conducted an online survey of 351 U.S. adults with ≥1 mental health condition and care-seeking behaviors. Descriptive statistics and non-parametric tests were used to evaluate rural and non-rural differences in demographics, social determinants of health, current barriers to mental health treatment, and the perceived value of PDTs. Key limitations of this approach include self-reported rurality and digital access bias associated with online survey distribution.ResultsBarriers to mental healthcare impacted 60% of all rural respondents, and rurality was associated with unique challenges like lower incomes, lower education levels, substantial Medicaid enrollment, and further distances from care. Rural respondents were also more likely to be completely unfamiliar with digital apps for mental health treatment. 89% of all respondents thought PDTs could address at least one barrier to care and about 97% of respondents were likely to use a PDT recommended by their provider.DiscussionExisting gaps in care and positive perceptions towards PDTs demonstrate unique promise for these modalities to address unmet mental health needs. However, lower PDT familiarity among rural respondents suggests a need for provider intervention and policy reforms.